Spinal hydatid disease - (:unkn) unknown (SPRINGERNATURE, 2002)
Study design: Review article on spinal involvement of hydatid disease. Objectives: A better understanding of this rare but clinically challenging disease is intended. An overview of the epidemiology, pathogenesis, presentation and diagnosis of spinal hydatid disease is provided. Management problems and frequent pitfalls are discussed as well as current therapeutic options, results and outcome. Methods: Thirty-seven reports of spinal hydatid disease published between 1964 and 2000 were reviewed. Results: Most of the reported cases of spinal hydatid disease presented with spinal cord compression syndrome. Due to the relative rarity of the problem the diagnosis was frequently made during surgery. Surgical intervention by decompressive laminectomy was the most frequent first management. Reports of anterior procedures as well as spinal stabilization exist. Intraoperative prophylaxis to reduce spillage as well as pharmacotherapy were usually instituted. Results of surgery were generally reported to be poor. Progressive neurological and mechanical deterioration over the years was the most frequently reported disease course. Anecdotal reports of alternative management strategies exist. Conclusion: Spinal hydatid disease should be considered in the differential diagnosis of spinal cord compression syndrome in endemic countries and sought after with imaging and serology. Treatment is based on surgical decompression. Despite therapy the disease frequently relapses with progressive destruction of the vertebral column and neurological deterioration. Retention of spinal stability is the major long term concern. Overall outcome is poor with few reports of disease-free long term survival.
Keywords: echinococcus; spine; hydatid disease; spinal cord compression syndrome; CYST; ECHINOCOCCOSIS; PARAPLEGIA